Vows, Veils, and Masks : The Performance of Marriage in the Plays of Eugene O'Neill - Wynstra, Beth, 1979- (Book collections on Project MUSE., 2023)
"This book offers a fresh analytical approach to the plays of Eugene O'Neill with its attention to the engagements, weddings, and marriages so crucial to the tragic action in O'Neill's works. Specifically, the book examines the culturally-sanctioned traditions and gender roles that underscored marital life in the early 20th century and that still haunt and define love and partnership in the modern age. Analyzing and weaving in artifacts like advice columns, advertisements, theatrical reviews, and even the lived experiences of the actors who brought O'Neill's wife characters to life, Wynstra points to new ways of seeing and empathizing with those who are betrothed and new possibilities for reading marriage in literary and dramatic works. She suggests that the various ways women especially were, and still are, expected to divert from their true ambitions, desires, and selves in the service of appropriate wifely behavior is a detrimental performance and one at the crux of O'Neill's marital tragedies. Wynstra's study invites more inclusive and nuanced ways of thinking about the choices married characters must make and the roles they play both on and off the stage"--